Counting with understanding? What is at stake in debates on researching domestic violence - Myhill, Andy (Criminology & criminal justice, 2021)
This article addresses recent debates relating to the measurement of domestic violence, and in particular the ‘domestic violent crime’ framework proposed by Sylvia Walby and colleagues. We argue for the utility of coercive control as a framework for measurement of domestic violence, and highlight what we see as misrepresentation of this concept in the work of Walby and colleagues. We also point to the limitations of traditional crime codes in capturing the range of abuse suffered by victims of coercive control, and question whether measuring physical assault is any more straightforward in sample surveys than measuring non-violent forms of coercion. We conclude by calling for greater attention to qualitative narratives and practice-based knowledge to ensure that measurement frameworks reflect the lived experiences of victim-survivors.